The Religious Connotations of the Sovereign in Destitution in the Malay Hikayat - Taslim, Noriah (Malay Literature, 2014)
The essay is an attempt to highlight the significance and the extent of religious influence on classical Malay literature. It plans to do this through the analysis of the structural elements of the plot at both at the surface and underlying level. To narrow down the analysis, only one genre of Malay literature, the so-called hikayat romance will be taken as corpus of investigation. To allow room for a more comprehensive analysis within this restricted corpus, two types of hikayat romance will be taken to task; these are the fantasy/court romance and the hagiographical romance. Both of these works are suitable for this study as they exhibit a remarkable level of religious influence in their textual elements. The analysis, however, will focus especially on the "exile motif" which is the controlling and generative element in the plot. Keywords: hikayat romance, generic structure, exile motif, Hindu interpretative model, sufistic interpretative model